Coagulation disorders in myocardial infarction with nonobstructive coronary arteries - A. S. Pisaryuk; A. A. Filkova; E. S. Tukhsanboev; G. S. Svidelskaya; A. A. Ignatova; E. A. Ponomarenko; A. A. Martyanov; A. A. Tarakanova; I. A. Meray; M. A. Panteleev; A. N. Sveshnikova; Z. D. Kobalava (Столичная издательская компания, 2024)
Aim. To investigate the state of the platelet and plasma components of hemostasis in patients with myocardial infarction with non-obstructive coronary arteries (MINOCA).Material and methods. The study included 42 patients with non-ST-segment elevation myocardial infarction (NSTEMI): MINOCA (n=24) and MI-CAD (n=18). Platelet aggregation ability in response to activation was evaluated using Solar AP2110 and LASCA aggregometers. Platelet functional activity and calcium signaling were assessed using flow cytometry methods. The plasma component of hemostasis, in addition to routine coagulation tests was evaluated using the global coagulation test "Thrombodynamics". The control groups for tests consisted of healthy volunteers.Results. When analyzing the ability of platelets to form aggregates by the aggregometry tests, it was found that platelets in the MINOCA group formed aggregates significantly worse upon ADP stimulation at various concentrations compared to the MI-CAD group. However, when platelets were stimulated with collagen, the opposite effect was observed: in the MI-CAD group, there was a noticeable decrease in aggregate formation in terms of light scattering amplitude compared to the MINOCA group. Flow cytometry using the functional platelet activity test protocol revealed that both groups showed a significantly increased platelet size after activation, reduced platelet granularity) both at rest and upon activation, significantly decreased number of procoagulant phosphatidylserine-positive platelets, and reduced dense granule release upon activation compared to healthy volunteers. The calcium signaling test showed a weakened calcium release in response to ADP in the MINOCA group compared to the MI-CAD group. In the study of the plasma component, no significant differences between the groups or deviations were found according to both routine tests and the "Thrombodynamics" test.Conclusion. Platelet activity did not differ significantly between the MINOCA and MI-CAD groups; however, in the MINOCA group, platelet activity was lower in some tests compared to the MI-CAD group. In the study of the plasma hemostasis component, normocoagulation was recorded in both groups.